The woman in cabin 10 - Ware, Ruth (New York : Scout Press, 2016)
"From New York Times bestselling author of the "twisty-mystery" (Vulture) novel In a Dark, Dark Wood, comes The Woman in Cabin 10, an equally suspenseful and haunting novel from Ruth Ware--this time, set at sea. In this tightly wound, enthralling story reminiscent of Agatha Christie's works, Lo Blacklock, a journalist who writes for a travel magazine, has just been given the assignment of a lifetime: a week on a luxury cruise with only a handful of cabins. The sky is clear, the waters calm, and the veneered, select guests jovial as the exclusive cruise ship, the Aurora, begins her voyage in the picturesque North Sea. At first, Lo's stay is nothing but pleasant: the cabins are plush, the dinner parties are sparkling, and the guests are elegant. But as the week wears on, frigid winds whip the deck, gray skies fall, and Lo witnesses what she can only describe as a dark and terrifying nightmare: a woman being thrown overboard. The problem? All passengers remain accounted for--and so, the ship sails on as if nothing has happened, despite Lo's desperate attempts to convey that something (or someone) has gone terribly, terribly wrong
Booklist
Library Journal
Kirkus Reviews
Publishers Weekly
Keywords: Women journalists -- Fiction; Cruise ships -- Fiction; Psychological fiction; Suspense fiction; Mystery fiction